UJI POTENSI DAUN BABADOTAN (Ageratum conyzoides L.) SEBAGAI INSEKTISIDA BOTANI TERHADAP HAMA (Plutella xylostella L.) DI LABORATORIUM - Nurhudiman Nurhudiman; Rosma Hasibuan; Agus M. Hariri; Purnomo Purnomo (Jurnal Agrotek Tropika, 2018)
Diamond back moth (Plutella xylostella) [Lepidoptera: Plutellalidae] is the most important pest of Brasisca vegetable in many part of area in Indonesia. Pest control of this pest has been relied on the use of synthetic insecticide. However prolog use of insecticide cause ecological and economical problems. There is a need for pest control that are sustainable and eviromentally sound. The use of natural (botanical insecticide) such as Ageratum conyzoides is expected to solve that problem. The objective of this research was to test the capability of goatweed suspension to cause mortality P. xylostella larvae and to measure toxicity level (LC50 and LT50) of Ageratum extract. This research was conduched during Juli 2016- February 2017 in green house and laboratory. The results indicated that all of concentration of goatweed (1-5%) was able to cause mortality onP. xylostella larvae. The lethal concentration for 50% mortality (LC50) value was 2,0254%. While the time need to kill 50% of P. xylostella larva were: 33.31 h, 20.68 h, 21.09 h, 12.65 h, 10.86 h treated by concentration of: 1%, 2%, 3%, 4% and 5% respectively. This study indicated the potential use of Ageratum extract to contol P. xylostella.